KINERJA APARATUR PEMERINTAH DAERAH PASCA RESTRUKTURISASI PADA KANTOR KELUARGA BERENCANA DAN PEMBERDAYAAN PEREMPUAN KABUPATEN TABANAN PROVINSI BALI - I Gede Eko Putra Sri Sentanu, Mr. (FIA UB, 2012)
That structuring the organization conducted the regional body of local government is a form of implementation of government policies in order to create an effective and efficient organization and implementation of local government administrative system. Tabanan Government has implemented its Reorganization under Regulation No local devices. Year 2008 3 Which refer to the PP No. 41 Year 2007 About the Organization of the Region, one is to form the Office of Family Planning and Women Empowerment (KB and PP). By establishing an office for matters of family planning and womens empowerment is meant to create a poor organizational structure in rich functionality but without leaving the area as prescribed that are required by the legislation in force. The results of this study indicate that the performance of the government apparatus of blood on KB and PP Office Tabanan views of: (a) Actual placement of employees after the restructuring of the regional organization under the PP. 41 Year 2007, Which Is Generally seen from the form and structure of organizational and structural or functional positions are in office positions That is, (2) The performance of the local government apparatus after the organizational restructuring and realization of the device with the placement officers Messenger Performance Commitment Program (KKP) as performance indicators and performance evaluation apparatus apparatuses, (3) The factors